Incidence and Risk Factors of Deep Vein Thrombosis in Hospitalized COVID-19 Patients. (28th August 2020) - Yu, Yuan; Tu, Jie; Lei, Bingxin; Shu, Huaqing; Zou, Xiaojing; Li, Ruiting; Huang, Chaolin; Qu, Yali; Shang, You
Deep vein thrombosis (DVT) is prevalent in patients with coronavirus disease 2019 (COVID-19). However, the risk factors and incidence rate of DVT remains elusive. Here, we aimed to assess the incidence rate and risk factors of DVT. All patients diagnosed with COVID-19 and performed venous ultrasound by ultrasound deparment between December 2019 and April 2020 in Wuhan Jin Yin-tan hospital were enrolled. Demographic information and clinical features were retrospectively collected. Notably, a comparison between the DVT and the non-DVT groups was explored. The incidence rate of venous thrombosis was 35.2% (50 patients out of 142). Moreover, the location of thrombus at the proximal extremity veins was 5.6% (n = 8), while at distal extremity veins was 35.2% (n = 50) of the patients. We also noted that patients with DVT exhibited a high level of D-dimer (OR 10.9 (95% CI, 3.3-36.0), P < 0.001), were admitted to the intensive care unit (OR 6.5 (95% CI, 2.1-20.3), P = 0.001), a lower usage of the anticoagulant drugs (OR 3.0 (95% CI, 1.1-7.8), P < 0.001). Finally, this study revealed that a high number of patients with COVID-19 developed DVT. This was observed particularly in critically ill patients with high D-dimer levels who required no anticoagulant medication.